Formation of the Kokchetav subduction–collision zone (northern Kazakhstan): Insights from zircon U–Pb and Lu–Hf isotope systematics - Glorie, S.; Zhimulev, F.; Buslov, M.; Andersen, T.; Plavsa, Diana; Izmer, A.; Vanhaecke, J.; De Grave, J. (Elsevier Science BV, 2014)
The Kokchetav subduction–collision zone is located in the western part of the ancestral Central Asian Orogenic Belt. This zone is built up by the Precambrian Kokchetav microcontinent which includes a HP–UHP metamorphic belt, and the North Kokchetav tectonic zone (NKTZ) which represents an accretionary complex between the Kokchetav microcontinent and the adjacent Stepnyak island-arc. The entire region is widely intruded by Palaeozoic granitoids which were emplaced after the collision of the Stepnyak island-arc with the Kokchetav microcontinent. We present zircon U–Pb ages and Lu–Hf systematics in zircon to better characterize the tectonic evolution of the Kokchetav subduction–collision zone.The Lu–Hf results indicate that the Kokchetav basement rocks are derived from late Neoarchaean — early Palaeoproterozoic (~ 2.5 Ga) crust. For the granite-gneiss basement of the Kokchetav microcontinent, early Mesoproterozoic (Grenville-age, ~ 1.17–1.14 Ga) zircon U–Pb crystallization ages were obtained. For the NKTZ, two main age-components were recognized: (1) an oldest Mesoproterozoic age-component (~ 1.20–1.05 Ga) similar as for the Kokchetav microcontinental zircons, and (2) a younger Early Cambrian (540–520 Ma) or Late Cambrian – Early Ordovician (~ 490–480 Ma) age-component. Th/U ratios (< 0.1) are indicative of a metamorphic origin for both Early Cambrian and Late Cambrian – Early Ordovician zircon populations. The oscillatory zoned Mesoproterozoic zircons have higher Th/U ratios (> 0.1) and are typical of a magmatic protolith. The distinction between both zircon types is supported by characteristic cathodoluminescence images. These results confirm previous observations, indicating early Palaeozoic high-grade metamorphism (~ 540–520 Ma) and collisional deformation (~ 490–480 Ma) of the Mesoproterozoic Kokchetav zone as a result of subduction–accretion and collision of the Stepnyak island-arc to the Kokchetav microcontinent. For two additional samples of the Balkashin granitic complex Early Devonian (~ 415–395 Ma) zircon crystallization ages (magmatic Th/U ratios) were obtained. The occurrence of a Mesozoic xenocryst within these leucogranites may indicate that they were emplaced in a continental-arc setting